4(x+6)-3x-2=5(2-2x)

Simple and best practice solution for 4(x+6)-3x-2=5(2-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+6)-3x-2=5(2-2x) equation:


Simplifying
4(x + 6) + -3x + -2 = 5(2 + -2x)

Reorder the terms:
4(6 + x) + -3x + -2 = 5(2 + -2x)
(6 * 4 + x * 4) + -3x + -2 = 5(2 + -2x)
(24 + 4x) + -3x + -2 = 5(2 + -2x)

Reorder the terms:
24 + -2 + 4x + -3x = 5(2 + -2x)

Combine like terms: 24 + -2 = 22
22 + 4x + -3x = 5(2 + -2x)

Combine like terms: 4x + -3x = 1x
22 + 1x = 5(2 + -2x)
22 + 1x = (2 * 5 + -2x * 5)
22 + 1x = (10 + -10x)

Solving
22 + 1x = 10 + -10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10x' to each side of the equation.
22 + 1x + 10x = 10 + -10x + 10x

Combine like terms: 1x + 10x = 11x
22 + 11x = 10 + -10x + 10x

Combine like terms: -10x + 10x = 0
22 + 11x = 10 + 0
22 + 11x = 10

Add '-22' to each side of the equation.
22 + -22 + 11x = 10 + -22

Combine like terms: 22 + -22 = 0
0 + 11x = 10 + -22
11x = 10 + -22

Combine like terms: 10 + -22 = -12
11x = -12

Divide each side by '11'.
x = -1.090909091

Simplifying
x = -1.090909091

See similar equations:

| 3m+5=11 | | 4(x+6)-3x-2=(2-2x)-x | | 36=85-25+15x+8Y | | (6X+X^6)(6x)= | | x^2=-15+8x | | 3y-9=7+2v-v | | 5x^2+6xy+5y^2-4=0 | | 4z^2-144=0 | | 2x^2=-5x-7 | | 2t^2+5t-3z=0 | | 2(3x-1)+5(2x+3)= | | x-81=0 | | m^2-5m+4=0 | | Sxs= | | Exg= | | x^2-16x=-7 | | 2e+e+4e= | | 3c+6+5c= | | 5a+6m+3a+8m= | | (8s+9)2=64 | | 4x-2(1-x)=2(3x-2) | | 12x^2+29x+15=0 | | 12y-16=20y | | 3x-5+2x+1=3+6 | | 11-8x=113-29x | | 32x^2-54x-5=0 | | 10z^2+19z=-6 | | 19x+21x=40 | | 1/4(12x+16)=10-3(x-2) | | 75+100=550 | | 4x^2+5=41 | | -24+x+8=4 |

Equations solver categories